Adjustment and age through the eyes of portuguese and english community dwelling older adults - von Humboldt, Sofia (2012)
To analyze subjective age (SA) and the contributors to adjustment to aging (AtA) identified by older adults and to investigate the latent constructs that can work as major determinants in SA and AtA in an older population. Method: Measures were completed, using a variety of appropriate methods, including demographics and interviews. Complete data were available for 108 older adults aged between 75-99 years (M = 81.1; SD = 6.43). Data was subjected to content analysis. Representation of the associations and latent constructs were analyzed by a Multiple Correspondence Analysis (MCA). Results: The most prevalent response of the interviewed participants for contributors to AtA was ‘sense of limit and existential issues’ (20.2%). ‘With congruence’ (29.3%) was identified as the most frequent SA response. AtA and SA for Portuguese elderly were explained by a three-factor model: ‘integrated’, ‘involved’ and ‘youngat- heart’. A three-dimension model formed by ‘attentive’, ‘driven’ and ‘connected’ was indicated as a best-fit solution for English elderly. Conclusions: AtA is related to SA in older adults in both samples. The results presented in this paper stressed the under-developed potential of an adjustment and age overall model for this population.